2023
DOI: 10.48550/arxiv.2303.15935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When Brain-inspired AI Meets AGI

Abstract: The human brain is widely considered one of the most intricate and advanced information-processing systems in the world. It comprises over 86 billion neurons, each capable of forming up to 10,000 synapses with other neurons, resulting in an exceptionally complex network of connections that allows for the proliferation of intelligence. Along with the physiological complexity, the human brain exhibits a wide range of characteristics that contribute to its remarkable functional capabilities. For example, it can i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Some prominent examples of LLMs include Bloom [35], OPT [36], LLAMA [37], ChatGPT [29], GPT-4 [32] and Palm 2 [38]. Indeed, the fame of ChatGPT has revolutionized and popularized NLP, leading to new research [39]- [42] and applications [43], [44] with LLMs as foundational models [45].…”
Section: Large Language Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some prominent examples of LLMs include Bloom [35], OPT [36], LLAMA [37], ChatGPT [29], GPT-4 [32] and Palm 2 [38]. Indeed, the fame of ChatGPT has revolutionized and popularized NLP, leading to new research [39]- [42] and applications [43], [44] with LLMs as foundational models [45].…”
Section: Large Language Modelsmentioning
confidence: 99%
“…Prior work has shown that language models perform better when the source and target domains are highly relevant [8], [24], [29], [45]- [47]. In other words, pre-training BERT models with in-domain corpora can significantly improve overall performance on a wide variety of downstream tasks [24].…”
Section: Domain-specific Language Modelsmentioning
confidence: 99%
“…Transformer [1] was first proposed for translation tasks in NLP, which combines Multi-head Self Attention (MSA) with Feed-forward Networks (FFN) to offer a global perceptual field and multi-channel feature extraction capabilities. The subsequent development of the Transformer-based BERT [67] proved to be seminal in NLP, exhibiting exceptional performance across multiple language-related tasks [15,25,68]. Leveraging the great flexibility and scalability of the Transformer, researchers have started to train larger Transformer models, including GPT-1 [4], GPT-2 [5], GPT-3 [20], GPT-4 [22], T5 [3], PaLM [69], LLaMA [70] and others.…”
Section: Foundation Modelsmentioning
confidence: 99%
“…Notable examples include GPT-3 [20], ChatGPT [21], GPT-4 [22], and others [23], including domain-specific large language models [24]. This ability to generalize across multiple downstream tasks without explicit training, commonly known as zero-shot generalization, represents a groundbreaking advancement in the field [13,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…We believe this database is of particular importance in the age of Artificial General Intelligence (AGI) (Bubeck et al, 2023;Zhao et al, 2023;Liu et al, 2023a). Successful large language models (LLM) such as ChatGPT, GPT-4, LLAMA (Touvron et al, 2023) and PaLM (Chowdhery et al, 2022) are trained on vast amounts of public domain data.…”
Section: Introductionmentioning
confidence: 99%